Implementasi Location Based Advertising Sebagai Media Promosi Pada Rumah Jamur Takalar - Ilsan, Mais; Husain, Tsalis Kurniawan; Thamsi, Alam Budiman; Amran, Farizah Dhaifina (Universitas Pahlawan Tuanku Tambusai, 2023)
This community service activity involves MSME Rumah Jamur Takalar as the partner. The partner's problem is the lack of knowledge and skills in marketing their products via online platforms and the business location/business name is not yet known by the people of Takalar. The purpose is to help the partner expand their market reach. The specific target to be achieved is the implementation of Location Based Advertising (LBA) as a means of partner’s promotion. The methods that used are mediation and training methods. The result of this activity is that Rumah Jamur Takalar has successfully registered and activated their business account on My Ads Telkomsel as a platform that provides LBA (Location Based Advertising). The results of LBA's performance as a promotional media show that LBA activities are 100% successful in delivering advertising content according to specific target locations (Takalar Regency and its surrounding areas).